2018
DOI: 10.3389/fimmu.2018.02200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Immunological Synapse in Differential Effects of APC Subsets in Alloimmunization to Fresh, Non-stored RBCs

Abstract: Background: Each year, over 5 million red blood cell (RBC) transfusions are administered to patients in the USA. Despite the therapeutic benefits of RBC transfusions, there are associated risks. RBC-specific alloantibodies may form in response to antigenic differences between RBC donors and recipients; these alloantibodies can be a problem as they may mediate hemolysis or pose barriers to future transfusion support. While there is currently no reliable way to predict which RBC recipients will make an alloantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Both splenic DCs and macrophages phagocytose allogeneic murine RBCs (90, 91) and because splenic macrophages clear endogenous aged RBCs, it had been assumed that macrophages also regulate the adaptive immune response (92). However, more recent studies have concluded that DCs are the primary APC for initiating the allogeneic response to RBCs (47, 93).…”
Section: Innate Control Of Adaptive Immunity To Insults In the Spleenmentioning
confidence: 99%
“…Both splenic DCs and macrophages phagocytose allogeneic murine RBCs (90, 91) and because splenic macrophages clear endogenous aged RBCs, it had been assumed that macrophages also regulate the adaptive immune response (92). However, more recent studies have concluded that DCs are the primary APC for initiating the allogeneic response to RBCs (47, 93).…”
Section: Innate Control Of Adaptive Immunity To Insults In the Spleenmentioning
confidence: 99%
“…Multiple studies have shown that macrophages (from the spleen and liver) consume the majority of RBCs in circulation 5–7 . However, despite significant erythrophagocytosis, RBC‐containing macrophages do not stimulate an immune response; indeed, even in response to allogeneic RBCs, macrophages fail to form productive synapses with T cells and do not elicit activation or proliferation 15 . As such, it is not surprising that macrophages do not play a significant role in priming OTII CD4 + T cells to HOD RBC‐derived autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes were harvested and processed 18 to 24 hours after transfusion, stained with antibodies to delineate APCs, and CD8 + and CD8 − DCs were sorted. Sorted DiO + DC subsets were cocultured at a 10:1 ratio with enriched OTII CD4 + T cells, as described previously 15 . OTII CD4 + T cells cultured in media alone served as a negative control, whereas stimulation with phorbol 12‐myristate 13‐acetate (PMA; 10 ng/mL) plus ionomycin (1 μg/mL) was a positive control for proliferation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations